Structure-activity relationship (SAR) studies on the mutagenic properties of 2, 7-diaminofluorene and 2, 7-diaminocarbazole derivatives. (1st January 2021) - Kim, Byeong Wook; Lee, Hwa; Keum, Gyochang; Kim, B. Moon
Graphical abstract: Abstract: We discovered that 2, 7-diaminofluorene or 2, 7-diaminocarbazole moiety can be employed as a core structure of highly effective NS5A inhibitors that are connected through amide bonds to proline-valine-carbamate motifs. Amide bonds can be easily cleaved via various metabolic pathways upon administration into the body, and metabolites containing 2, 7-diaminofluorene and 2, 7-diaminocarbazole core structures have been known to be strong mutagens. To avoid the mutagenesis issue of these core structures, we examined various functional groups at the C9 or N9 position of 2, 7-diaminofluorene or 2, 7-diaminocarbazole, respectively, through the Ames test in TA98 and TA100 mutants of Salmonella typhimurium LT-2. We discovered that, through proper alkyl substitution at the C9 or N9 position, 2, 7-diaminofluorene and 2, 7-diaminocarbazole moieties can be successfully employed in drug discovery without necessarily causing mutagenicity problems.